Pesticide residue distribution in citrus fruits: Effectiveness of peeling as a mitigation strategy - Mohrah Alenazi; Abdulmajeed Al-Zaid; Jebrel Najai; Abdulrahman AL-Dossari; Abdulah Al-Batti; Fahad Al-Bahouth (Environmental Pollution and Management)
This study investigates the levels of pesticide residues in peeled and unpeeled citrus fruits, comparing local and imported varieties, to assess the impact of peeling on residue reduction. A total of 80 citrus samples, including 40 local fruits (orange, mandarin, lemon, citron) from the Alhariq Citrus Festival and 40 imported fruits (orange, mandarin, lemon) from supermarkets in Riyadh, were analyzed. Pesticide residues were extracted using the QuEChERS method and quantified by liquid chromatography coupled with QTRAP quadrupole mass spectrometry (LC-MS/MS), evaluating 316 pesticide residues based on SFDA regulations (SFDA.FD 382:2019). Results showed that all local samples were free of detectable pesticide residues. In contrast, 95 % of imported samples contained residues within permissible limits, while 5 % exceeded maximum residue levels. Nineteen pesticides were detected, with Imazalil (n = 33), Thiabendazole (n = 27), and Chlorpyrifos (n = 10) being the most prevalent. Notably, peeling reduced pesticide levels by 82 % (Thiabendazole, Imazalil) to 100 % (Chlorpyrifos), highlighting its effectiveness in residue removal. These findings emphasize the need for residue monitoring across all citrus fruit layers and stricter regulatory oversight of imported fruits to ensure consumer safety.